Research on Application of Cold Chain Logistics Management Based on Big Data Technology - Li Na (E3S Web of Conferences, 2021)
Compared with developed countries, the cold chain logistics of agricultural products in china is wasteful, which not only consumes a lot of labor and natural resources, but also reduces the domestic and international competitiveness of agricultural products. The paper analyzes outstanding issues such as cold chain "broken chain", "information islands", and cold chain "food safety". Through the integration of advanced information technologies such as big data and mobile internet, a cold chain logistics engineering management technology platform is established to establish a national The data analysis center and the national cold chain logistics big data real-time monitoring and early warning platform, open up the logistics information chain, realize the full traceability of logistics information, promote the effective docking of logistics information and public service information, and encourage the sharing of information on logistics platforms between regions and industries. interconnection.